2011
DOI: 10.4028/www.scientific.net/amr.347-353.81
|View full text |Cite
|
Sign up to set email alerts
|

Application of PV Window for Office Building in Hot Summer and Cold Winter Zone of China

Abstract: In this paper, three kinds of PV glazing system applied to office building of Shanghai which located in hot summer and cold winter zone of China were studied. Building simulation software Energy Plus was used to simulate thermal load, lighting electricity consumption, and PV electricity generation. According to the simulation results of annual electricity consumption, taking SC as the comparison basis, the saving rate of single PV glazing system (SPV) was 3.6%, double PV glazing system (DPV) was 4.8%, and natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Li peng [9] conducted a simulation study on a PV window with a fixed architectural assumption, and results showed a better overall performance achieved by PV glazings (includes single and double PV glazings) compared to clear glazings in four different climate zones. Another study [10] showed a similar result with an overall energy savings rate of 3.6% and 4.8% for single and double PV glazings respectively. Studies above indicated the importance of overall energy performance in evaluation of PV glazings, and revealed the great potential of PV glazings and facades in terms of energy saving.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Li peng [9] conducted a simulation study on a PV window with a fixed architectural assumption, and results showed a better overall performance achieved by PV glazings (includes single and double PV glazings) compared to clear glazings in four different climate zones. Another study [10] showed a similar result with an overall energy savings rate of 3.6% and 4.8% for single and double PV glazings respectively. Studies above indicated the importance of overall energy performance in evaluation of PV glazings, and revealed the great potential of PV glazings and facades in terms of energy saving.…”
Section: Introductionsupporting
confidence: 57%
“…When the daylight illuminance level is below 300 Lux, the artificial lighting will be activated and reach the required illuminance level, with the extra electricity consumption calculated by Energy Plus. To obtain the daylighting simulation results in Energy Plus, visible transmittance is required, as given in equation (10).…”
Section: Calculation Methods For a See-through A-si Pv Glazingmentioning
confidence: 99%